Components i organització d'una unitat amb un tractament integrat de llengua i continguts en una L2 - Pascual, Vicent (Caplletra. Revista Internacional de Filologia, 2008)
In an educational system like ours, with four curricular languages in compulsory education, language integrated treatment and its contents (TILC) has to become, undoubtedly, a privileged instrument for multilingual education, because it allows to fulfil two goals at the same time: to acquire contents of different academic disciplines and to simultaneously provide competences in the language or languages with which these contents are developed.This article describes the concept of integrated language treatment and contents; the main components of this approach are also analyzed from a didactic point of view; and finally all the aspects studied will be used in the structuring of a thematic unit thatincludes disciplinary contents of one or more areas conveyed in a L2 and that can be used in Primary and Secondary Education contexts.